Respuesta :
A = V1 - V0/t.....multiply both sides by t
At = V1 - V0....add V0 to both sides
At + V0 = V1
At = V1 - V0....add V0 to both sides
At + V0 = V1
For this case we have the following equation:
[tex]A = \frac{v1-v0}{t} [/tex]
From here, we must clear the value of v1.
For this, we follow the following steps:
1) Pass variable t to multiply:
[tex]A*t = v1 - v0[/tex]
2) Add v0 on both sides of the equation:
[tex]A*t+v0=v1-v0+v0[/tex]
3) Rewrite the expression:
[tex]A*t+v0=v1[/tex]
Answer:
The resolved expression for v1 is:
[tex]v1 = A*t+v0[/tex]
[tex]A = \frac{v1-v0}{t} [/tex]
From here, we must clear the value of v1.
For this, we follow the following steps:
1) Pass variable t to multiply:
[tex]A*t = v1 - v0[/tex]
2) Add v0 on both sides of the equation:
[tex]A*t+v0=v1-v0+v0[/tex]
3) Rewrite the expression:
[tex]A*t+v0=v1[/tex]
Answer:
The resolved expression for v1 is:
[tex]v1 = A*t+v0[/tex]